In-Situ Ionic Imprinted Membrane (IIM) Synthesis Based on Acetic Polyeugenoxy Acetyl Tiophen Methanolate for Gold(III) Metal Ion Transports - Muhammad Cholid Djunaidi; Pardoyo Pardoyo; Didik Setiyo Widodo; Retno Ariadi Lusiana; Anggun Yuliani (Universitas Gadjah Mada, 2020)
In this research, Polyeugenoxy Acetyl Tiophen Methanolate (PEATM)-Au ionic imprinted membrane (IIM) was synthesized. IIM is a PEATM based membrane that has Au(III) ion molds. The PEATM synthesis was analyzed using FTIR spectroscopy, and its relative molecular weight was determined by the viscometry method. To find out the presence of Au(III) templates on IIM, FTIR spectroscopy and SEM-EDX were used. The results of FTIR spectroscopy & SEM-EDX analysis prove the existence of Au(III) metal ion templates at IIM. Through FTIR spectra, it could be seen that the absorption area of the -OH group was widening. In the IIM, the CS group wave number (702.9 cm–1) also shifted to a larger wavenumber (848.68 cm–1), this is likely due to the presence of PEGDE as a crosslinker agent and PVA as a plasticizer on the membrane that interacts with PEATM-Au, which influences the shift of vibrational wavenumber of CS bonds. It was also found that the most effective pH of the feed phase for the transport was at pH 3, and the most optimum transport time was 24 h for IIM and 48 h for NIM. The transport of Au in binary mixture of Au/Cd, Au/Fe, and Au/Pb also proves that the presence of Au(III) ions in IIM makes IIM more selective to Au(III) metal ions than NIM when used for the transport process as it transports Au more than the other metals. These results were as expected by using the HSAB theory as its groundwork.